Penerapan Profil Pelajar Pancasila Sebagai Upaya Membentuk Karakter Peserta Didik Kelas VA MIN 2 Kota Bengkulu - Distria, Olva; Azizah Irawan, Risa; Tiara Deka, Agustin; Yuliarti, Nadia (JPT : Jurnal Pendidikan Tematik, 2024)
In this research, the researcher intends to see how the analysis of the application of the Pancasila student profile is carried out as an effort to shape the character of students in the VA MIN 2 class in Bengkulu City. This research is research that uses qualitative descriptive methods, with the technique of giving questionnaires to students, interviews with teachers and students, and conducting observations. The data analysis technique uses descriptive analysis which is carried out with the aim of getting a picture of the data that the researcher will analyze. The research population and sample were all 31 students from class VA, consisting of 21 women and 10 men, where the sample had an average age of 11-12 years. The independent curriculum is a curriculum that has only just been implemented. This is the reason the author conducted research, namely to analyze the application of the Pancasila learning profile in the independent curriculum in elementary schools. The results obtained in this research were from the interviews discussed previously and the results of the questionnaire, each aspect of which reached more than 81%. And in accordance with the observations and documentation that researchers have carried out at MIN 2 Bengkulu City. Even though the implementation of the Pancasila student profile in MIN 2 Bengkulu City is still in the development stage, by cultivating the Pancasila profile, a national character will be embedded that is ready to face challenges and become better human beings and noble moral values will be created that can be realized.